Maturity in Agile Software Development - Fontana, Rafaela Mantovani; Reinehr, Sheila; Malucelli, Andreia (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2016)
This paper summarizes the main objectives, research approach, and contributions of the doctoral dissertation named as “Maturity in Agile Software Development”. It was developed in the Graduate Program in Informatics of the Pontifical Catholic University of Parana, from 2013 to 2015. The study was ́developed with the objective to characterize maturity in agile software development, as a means to guide agile teams in software process improvements. Our results contribute to the software engineering body of knowledge by showing a picture of maturity in agile teams that goes beyond defining and controlling processes, as usually stated by reference models.